Traffic Solution and Improvement for the Area Surrounding Shubra Museum in Taif City, KSA - Adil Mohammed Elhassan; Ahmed Abdelhafiz (Universitas Diponegoro, 2021)
Planning and design of road infrastructure are based on determination of traffic flow parameters and their distribution in the observed area in terms of space and time. For the purpose of selecting the optimal solution of the planned period, it is necessary to conduct research of relevant traffic flow parameters in characteristic conditions of the observed road network. Taif city is located in the western zone of the Kingdom of Saudi Arabia where it is the eastern port of the Holly Capital, Makkah. In addition, it is a major touristic destination for citizens throughout the year. Despite this importance, Taif city needs to develop traffic flow, especially in downtown because of high traffic congestion, traffic accidents, location of city and the increasing population annually. This paper shows the solution of traffic systems and improving of the area surrounding of Shubra museum in Taif City. The engineering calculations such the peak hour factor, peak hour volume and engineering designs of the roads, pedestrians and design of the parking to achieve the KSA vision 2030 taking into consideration national and global codes within the realistic constrains and reduce the cost as much as possible. The alternatives proposed were studied within the current road networks surrounding the Shubra Museum in downtown Taif to obtain the optimized alternative, in order to find a sustainable future traffic flow. The proposed alternatives based upon international and national standards for highways design, AASHTO, Highway Capacity Manual (HCM), American Society for Testing and Materials (ASTM) and Specifications of Saudi Ministry of Transportation. Results revealed that the proposed alternatives achieved better performance in terms of traffic regulation in downtown Taif city. Also, the wide area obtained around the museum showed a better performance in terms of organizing the pedestrian movement and the comfort of the visitors as well as the museum achieving its goals very efficiently in the future. Moreover, construction of tunnel reduces the traffic congestions in the future and increases the area on the front of museum by 60 %. Although the high cost of constructing a concrete tunnel in the front area of the museum which needs extensive geotechnical and structural studies, the positive environmental impacts give this alternative more advantages as a viable and sustainable alternative.